FREQUENCY OF PERITONEAL INFECTIONS AMONG PATIENTS UNDERGOING CONTINUOUS PARACENTESIS WITH AN INDWELLING CATHETER - Nadir, Abdul; Thiel, David H Van (Journal of Ayub Medical College Abbottabad, 2010)
Background: Ascites is a common clinical manifestation of advanced liver disease which can be managed with repeated large volume paracentesis. We sought to determine if continuous paracentesis via placement of an indwelling catheter for the management of ascites is safe and effective. Methods: We placed 38 peritoneal drainage catheters in 30 patients for durations ranging from 1-10 days. Patients underwent ascites fluid culture and cell count determinations immediately before and after the completion of paracentesis. Serum WBC count, BUN and creatinine levels were available on all patients before and after paracentesis. The descriptive data were analysed to assess the rate of peritoneal infections, change in renal function and ultimate clinical outcome of patients. Results: A mean 12.73 litres of peritoneal fluid was removed via continuous peritoneal drainage accomplished with the use of an indwelling abdominal catheter. Eight peritoneal cultures obtained after paracentesis grew out. The mean peritoneal cell count before and after paracentesis in each subject did not show evidence for spontaneous bacterial peritonitis. Five patients underwent successful liver transplantation (OLTX) and did not develop any peritoneal infections post OLTX. Conclusion: Continuous large volume paracentesis using an indwellingabdominal catheter for several days is effective in removing large volumes of peritoneal fluid in patients with endstage-liver-disease (ESLD). The peritoneal fluid can grow out bacteria if it is left in the abdomen for ‰¥3 days. Keywords: Large volume Paracentesis, indwelling